PENGARUH SERVANT LEADERSHIP TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA PEGAWAI (Studi pada Pegawai Negeri Sipil di RSUD Wangaya Kota Denpasar) - Kamanjaya, I Gede Hendry; Supartha, Wayan Gede; Dewi, IG.A. Manuati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017, 2017)
This study is focused to analyze the impact of servant leadership on employee performance in relation to the organizational commitment mediation. It is a causality research, providing an explanation and understanding about the impact of servant leadership on employee performance and the impact of servant leadership on organizational commitment. The sample of the research are 90 civil servants in Wangaya General Hospital as the respondents. In this study questionares are used as instuments of the research. Descriptive and inferential analysis were applied as method of analysis and Structural Equation Model-Partial Least Square (SEM-PLS) as a tool. The result is that servant leadership does not have any significant effect on employees performance, servant leadership has a positive and significant effect on organizational commitment, organizational commitment has positive and significant effect on employee performance, and the impact on servant leadership and employee performance through the role of organizational commitment as mediating variable is supported.
Keywords: servant leadership, organizational commitment, employee performance.